1998
DOI: 10.1038/1869
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of human serum albumin complexed with fatty acid reveals an asymmetric distribution of binding sites

Abstract: Human serum albumin (HSA) is the most abundant protein in the circulatory system. Its principal function is to transport fatty acids, but it is also capable of binding a great variety of metabolites and drugs. Despite intensive efforts, the detailed structural basis of fatty acid binding to HSA has remained elusive. We have now determined the crystal structure of HSA complexed with five molecules of myristate at 2.5 A resolution. The fatty acid molecules bind in long, hydrophobic pockets capped by polar side c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

51
1,234
1
8

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,291 publications
(1,294 citation statements)
references
References 24 publications
51
1,234
1
8
Order By: Relevance
“…S5), there is approximately one (1.1 ± 0.3) free SLFA in the buffered solution. This is consistent with the fact that there are seven FA binding sites on HSA [9] and eight SLFAs are present.…”
Section: Binding Of Complex 5 In Presence Of Long-chain Fatty Acids: supporting
confidence: 90%
See 1 more Smart Citation
“…S5), there is approximately one (1.1 ± 0.3) free SLFA in the buffered solution. This is consistent with the fact that there are seven FA binding sites on HSA [9] and eight SLFAs are present.…”
Section: Binding Of Complex 5 In Presence Of Long-chain Fatty Acids: supporting
confidence: 90%
“…Among the blood proteins, human serum albumin (HSA) is the most abundant (~630 mM) and can serve as a transport vehicle for various compounds including fatty acids (FAs), bilirubin, steroids, metal ions, and various pharmaceuticals [8]. There are seven distinct binding sites on HSA for long-chain FAs (FA1 -FA7) distributed throughout the protein in an asymmetric way [8], of which FA2, FA4, and FA5 are the highest affinity sites, as indicated by crystallographic studies [9]. The principal regions of exogenous drug binding sites are located in hydrophobic pockets in subdomains IIA and IIIA (site I and site II, respectively according to the conventional view based on Sudlow's classification) [8,10], and in the recently identified binding pocket within subdomain IB (site III) which is considered as the third major binding site [11].…”
Section: Interaction Of Anticancer Metallodrugs With Proteins Is Of Cmentioning
confidence: 99%
“…Not much electron density was observed in the FA site 1 located in subdomain IB, consistent with the proposal that this site is a weak FA binding site. 13,14 In the FA site 6 and site 7 (Sudlow site I), the electron densities [ Fig. 2(A,B)] were much larger than what typically observed for myristate and were modeled with confidence to DAUDA molecules, which has a large dansyl head group compared with myristate.…”
Section: Reliability Of the Rhsa-myr-dauda Structurementioning
confidence: 95%
“…5,11,12 In addition, a total of seven major fatty acid (FA) binding sites in defatted HSA are also identified mainly through the extensive works by Curry. 6,13,14 These FA binding sites distributed across the protein and are available for the binding of exogenous compounds. FA sites 2, 4, and 5 on HSA were proposed to have the high affinity toward FA.…”
Section: Introductionmentioning
confidence: 99%
“…Albumin reacts with nitric oxide to form a stable Snitrosothiol that has endothelium-derived relaxing factor-like properties (Keaney et al, 1993). Albumin also plays a crucial role in binding and transport of fatty acids (Curry et al, 1998). We have shown that albumin reduces ischemic brain swelling (Belayev et ).…”
Section: Part Ii: Neuroprotection --Moving From the Present Into The mentioning
confidence: 99%